The Impact of International Oil Price on Electricity Consumption and Output: A Case of Manufacturing Sector in Malaysia - Husainia, Dzul Hadzwan; Hooi, Hooi Lean (School of Social Sciences, USM, 2014)
This paper investigates the impact of international oil price on output and electricity consumption in the manufacturing sector in Malaysia. Wefound that electricity consumption, output and the international oil price are cointegrated in the long run. The relationship between electricity consumption and output is significantly positive. In the long run, we found a unidirectional causality runs from output to electricity consumption. This result indicates that the development of manufacturing sector stimulates greater demand for electricity. Government needs to make sure that the future planning of electricity supply is in line with the economic development planning to avoid shortage in electricity supply. Focusing more on industrial development policy to promote growth in manufacturing sector is recommended since energy conservation is expected not to give an adverse impact to the output growth. In the short run, there are two unidirectional relationships exist, 1)from the international oil price to electricity consumption,and 2) from international oil price to manufacturing output. A shock in international oil price might affect both electricity consumption and output growth in the short run only.